Formulation and Evaluation of Canagliflozin Self-nanomicellizing Solid Dispersion Based on Rebaudioside A for Dissolution and Solubility Improvement - Nizar Awish Jassem; Shaimaa Nazar Abd Alhammid (Iraqi Journal of Pharmaceutical Sciences, 2025)
Self-nanomicellizing solid dispersion is a new formulation that combines the advantages of solid dispersion and nanomicelles strategies to increase drug oral bioavailability. The strategy involves utilizing a suitable carrier to create a solid dispersion that self-assembles into nanomicelles when it comes into contact with gastrointestinal fluids. Rebaudioside A is a steviol glycoside that has been reported to possess nano carrier-like characteristics by being self-assembled into nanomicelles in aqueous solutions. Canagliflozin is a novel sodium-glucose cotransporter-2 inhibitor approved for treating patients with type 2 diabetes. Its oral administration is associated with variable and poor absorption, owing primarily to insolubility in aqueous media. This work aimed to develop canagliflozin self-nanomicellizing solid dispersion systems to overcome its pharmaceutical limitation and enhance oral bioavailability. The solvent evaporation method was selected to prepare a self-nanomicellizing solid dispersion system of canagliflozin. Rebaudioside A was chosen as a nanocarrier after screening several polymers for their ability to improve the solubility of canagliflozin by phase solubility study. The optimized formulations were characterized by solid-state analysis, dissolution studies, particle size distribution, and TEM. The study demonstrates that the self-nanomicellizing solid dispersion of canagliflozin, based on Rebaudioside A (FR5), has a 69.7 nm spherical particle size, stable distribution upon 20-fold dilution, and improved aqueous solubility by over 753.5-fold due to nanomicellization, as determined through scanning calorimetry, X-ray diffraction, dynamic light scattering, and transmission electron microscopy. Moreover, there is a significant enhancement of dissolution rate compared with the physical mixture (PM) and pure drugs, as indicated by higher values of f1 and lower values of f2, which are obtained. The optimized formula of canagliflozin self-nanomicellizing SD (FR5) dissolved well after 30 minutes and demonstrated higher dissolution efficiency (DE) than the intact canagliflozin and physical mixture. The DE% parameter confirms these findings (DE30,FR5 = 70.34%, DE30,PM = 21.91%, and DE30,pure drug = 18.28%. Fourier transform infrared spectroscopy reveals mild interactions between the drug and the excipient due to hydrogen bonding, favoring the formation of a stable solid dispersion system with negligible chemical interactions. The study indicates that optimized canagliflozin self-nanomicellizing sold dispersion systems using rebaudioside A are promising methods for improving oral bioavailability.